Modeling an Intelligent Agriculture System Simulation Based on Mobile Cloud Internet of Things (IoT) - Susilo, Susilo; Abadi, Surjo (Prodi Teknik Elektro FT UKI, 2021)
Intelligent systems based on the Internet of Things (IoT) used for analysis and monitoring needs are present in all areas of human life and agriculture. Through the smart system was created, it can provide recommendations for management and also improving for agricultural and livestock production. Monitoring is done by collecting data (data collecting) and being modeled from several temperatures, humidity, gas, distance measurement, light indicators. The concept of E-Agriculture (Electronic Agriculture) is limited to monitoring environmental conditions of agricultural production and also provides an overview of E-Agriculture or E-Farm modeling on a larger scale. The E-AgriFarm intelligent system simulation using Arduino Controller and Blynk's Cloud IoT has a temperature measurement range of 26 - 31 0C, Relative humidity (RH) from 47% - 64%, and detection of a water level of at least 40-50 cm meters for drinking containers for each livestock with a capacity of 20 liters, and the systems can detect the level of pollution of gas leaks. Thus the E-AgriFarm smart system can provide management recommendations and increase the livestock production system to be better monitored and controlled.